Ecotoxicological effects of pharmaceutical preparations and the possibility of removing them through phytoremediation: A review - Abdul – Jabbar, Ruaa M.; Al-Adily, Batool M.; Kadhim, Nuha F. (Edelweiss Applied Science and Technology, 2024)
From several decades, there was a significant increase in the production of pharmaceuticals due to their widespread use for both animal and human health. However, these pharmaceuticals also release large amounts of waste into the water environment, where they have been found at levels of ng/l to mg/l in wastewater and surface water. Additionally, because pharmaceuticals initially have biological effects such endocrine disruption, they may have a multitude of adverse effects. Hospitals are indicated or thought to be a significant and extremely variable source that is typically released into sewers immediately, without any kind of preparation. even if they only make up a minor portion of the influents of sewage treatment plants’ overall effluent volume. One of the primary sources of pharmaceuticals that are present in every area of the environment is the hospitals. These medications were transferred to wastewater treatment plants (WWTPs), which lack the necessary equipment to effectively handle these kinds of substances. Pharmaceutical contamination of water is regarded as a growing pollution issue in developed nations as these pollutants and micropollutants have been introduced into drinking water sources. In order to raise awareness among physicians, patients, and pharmaceutical manufacturers that pharmaceutical materials may have side effects outside of the patient, certain countries have implemented a classification system for pharmaceutical drugs based on their propensity to accumulate in surface water and interfere with aquatic life. This program is assessed by yearly tests of pharmaceuticals in sewage treatment effluents. The results indicate the presence of numerous types of medicines, including trimethoprim, sulfamethoxazole, and metronidazole, in all analyzed sewer treatment plant effluents. The manufacturing and consumption of pharmaceuticals appear to have an impact on their presence in wastewater.